Optimal parameters of inverter-based microgrid to improve transient response - Sergio Andrés Pizarro Pérez; John E. Candelo-Becerra; Fredy E. Hoyos Velasco (Institute of Advanced Engineering and Science, 2020)
The inertia issues in a microgrid can be improved by modifying the inverter control strategies to represent a virtual inertia simulation. This method employs the droop control strategy commonly used to share the power of a load among different power sources in the microgrid. This paper utilizes a modified droop control that represents this virtual inertia and applies an optimization algorithm to determine the optimal parameters and improve transient response. The results show better control when different variations are presented in the loads, leading the microgrid to have a better control of the operation. The optimization method applied in this research allows improvement to the transient response, thus avoiding unnecessary blackouts in the microgrid.